Indicators of sustainable development of the economic ecosystem of the territory - E. V. Popov; I. P. Chelak; S. A. Kavetskiy (Управление)
The relevance of the problem under study is due to the fact that sustainable development of territories determines the possibilities of regional socio-economic development, and assessment of indicators of the sustainable development is a necessary aspect in public administration, allowing to establish the effectiveness of the implemented regional socio-economic policy, identify problems, outline ways to solve them, increase the competitiveness of the territory. A review of scientific literature and other materials related to the sustainable development of the territories and implementation of the sustainable development goals at the national level shows that there is a need to consider aspects of the sustainable development of the territories: social and economic. In this regard, we can see the increased relevance of monitoring and measuring the sustainability of the development of regional socio-economic systems, pace of change, determining the vector of the development of the main components and their interrelationships. The purpose of this article is to systematise the indicators of the sustainable development of the economic ecosystem of the territory. The territory is considered as an ecosystem, its main elements are highlighted which interact with each other and on which the sustainable development of the region, its competitiveness and the quality of life of residents directly depend. The paper presents the indicators, and on their basis the assessment of the level of the sustainable development of the territories is conducted. The interrelation between the elements of the economic ecosystem of the territory and indicators of its sustainable development is considered. The main concepts of sustainability are highlighted. New scientific results consist in the identification of the indicators of the sustainable development and their relationship with the major stakeholders of the ecosystem of the territory and its core. The results obtained develop opportunities in assessing the socio[1]economic development of the territories. The materials of the article are of practical value for assessing the sustainable development of Russian territories and identifying problems in the regional management. Their external environment is characterised by global socio-economic instability. In the current conditions, the assessment of the sustainable development of the territories becomes necessary in order to comprehensively study possible risks, identify problems and form an effective policy of the authorities.